A Sydnone-Based Route to Indazolo[2,3-a]quinoxaline Derivatives - Louis, Manon; Talbot, Alex; Lamaa, Diana; Sallustrau, Antoine; Audisio, Davide; Taran, Frédéric (Synlett, 2022)
A new synthetic route to indazolo[2,3-a]quinoxaline derivatives is described. The strategy is based on the 1,3-dipolar cycloaddition of arynes to quinoxaline–sydnone derivatives as a key step. The polyaromatic sydnones were prepared through a copper-promoted intramolecular cyclization of the C-4 position of sydnones on imines.
Keywords: sydnones; cycloaddition; quinoxalines; indazoloquinoxalines